Communal land and tenure security: analysis of the South African Communal Land Rights Act 11 of 2004 - Johnson, Ebrezia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (LLM (Private Law))--University of Stellenbosch, 2009.